Portuguese Citizens’ Support for Democracy: 40 Years after the Carnation Revolution - Sanches, Edalina (2016)
Forty years after the Carnation Revolution, the relatively young Portuguese democracy is experiencing dramatically low levels of public specific support for democracy. This article tests the leverage of demand-side and supply-side accounts to explain differentials in public satisfaction with democracy. Through ordinary least squares regression analyses that draw on the unique data of the ‘Barometer 40 Years of Democracy in Portugal (2014)’, this articles shows that age cohort, identification with extreme parties, evaluation of the country’s political past, and economic performance are strong correlates of citizens’ specific support for democracy